Factores que influyen en la educación inclusiva: camino a la igualdad = Factors influencing inclusive education: on the road to equality - Gomez Gomez, Maria Carmen (Revista Educação Por Escrito)
The theme of inclusion is the classroom is something present in the school and in today’s society since the children of now are the men of the future. In this paper we will analyze what is inclusion and how the different educational laws have been progressing to implement it in the system. There is also a review of studies that analyze inclusion experiences and methodologies that are being applied in schools and favor the inclusion of all students in its broadest sense. We must educate on diversity, assume and support the right of all to a quality education, inclusion is not only a thing of the classrooms, it is a social challenge